Identification of Optimal Protocols for Sequencing Difficult Templates: Results of the 2008 ABRF DNA Sequencing Research Group Difficult Template Study 2008 - Kieleczawa, Jan (The Association of Biomolecular Resource Facilities, 2009)
The 2008 ABRF DNA Sequencing Research Group (DSRG) difficult template sequencing study was designed to identify a general set of guidelines that would constitute the best approaches for sequencing difficult templates. This was a continuation of previous DSRG difficult template studies performed in 1996, 1997, and 2003. The distinguishing factors in the present study were the number of DNA templates used, the number of different types of difficult regions tested, and the inclusion of a follow-up phase of the study to identify optimal protocols for each type of difficult template. DNA templates with associated sequencing primers were distributed to participating laboratories and each laboratory returned their sequencing results along with descriptions of the experimental conditions used. The data were analyzed and the best protocols were identified for each difficult template. This information was subsequently distributed to the participating laboratories for a second round of sequencing to evaluate the general applicability of the optimized protocols. The average improvements in sequencing results were 11% overall, with a range of −25% to +43% using the optimized protocols. The full results from this study are presented here and they demonstrate that general experimental protocols and common additives can be used to improve the sequencing success for many difficult templates.